2021
DOI: 10.1246/bcsj.20210109
|View full text |Cite
|
Sign up to set email alerts
|

AgBF4-Mediated Chlorine-Fluorine Exchange Fluorination for the Synthesis of Pentafluorosulfanyl (Hetero)arenes

Abstract: We report a new protocol to form pentafluorosulfanyl (hetero)arenes via chlorine-fluorine exchange of (hetero)aryl tetrafluorosulfanyl chlorides by AgBF4. The method enables access to electron-deficient pentafluorosulfanyl(hetero)arenes, which are targets that are difficult to synthesize. Two advantages of AgBF4 are its ease of handling and stability. This would be a general transformation protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…An alternative method for achieving the conversion of aryl- and heteroaryl-SF 4 Cl derivatives – obtained by treatment of the corresponding disulfides with KF/Cl 2 (excess) in acetonitrile – into SF 5 compounds was also developed by Shibata et al 20 Both SF 5 -aryl and -pyridyl products were prepared in moderate isolated yields by this method, based on the treatment of the corresponding SF 4 Cl substrates with AgBF 4 in DCM at room temperature (Scheme 18 ).…”
Section: Methods For Incorporation/manipulation Of Sf 4 ...mentioning
confidence: 99%
See 3 more Smart Citations
“…An alternative method for achieving the conversion of aryl- and heteroaryl-SF 4 Cl derivatives – obtained by treatment of the corresponding disulfides with KF/Cl 2 (excess) in acetonitrile – into SF 5 compounds was also developed by Shibata et al 20 Both SF 5 -aryl and -pyridyl products were prepared in moderate isolated yields by this method, based on the treatment of the corresponding SF 4 Cl substrates with AgBF 4 in DCM at room temperature (Scheme 18 ).…”
Section: Methods For Incorporation/manipulation Of Sf 4 ...mentioning
confidence: 99%
“…Scheme 16 Synthesis of SF5 pyridine aryliodonium reagent and SF5 heteroarylation of β-ketoester, pirrole and amine 18 Scheme 17 SF5 heteroarylation of phenols and thiols 18 An alternative method for achieving the conversion of aryl-and heteroaryl-SF4Cl derivatives -obtained by treatment of the corresponding disulfides with KF/Cl2 (excess) in acetonitrileinto SF5-compounds was also developed by Shibata et al 20 Both SF5-aryl and -pyridyl products were prepared in moderate isolated yields by this method, based on the treatment of the corresponding SF4Cl-substrates with AgBF4 in DCM at rt (Scheme 18).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…reported the synthesis of aryl‐ and heteroaryl‐S VI pentafluorides using HgO and HF (Scheme 32G) [77] . Very recently, the Cornella and Shibata groups independently showed that AgBF 4 is also a valid source of F for the synthesis or Ar−SF 5 compounds (Scheme 32H) [47, 78] . The authors proposed activation of the Cl atom of (hetero)aryl‐SF 4 Cl by Ag + , and subsequent attack of the fluoride atom of the BF 4 anion to the S center by either a concerted or stepwise mechanism.…”
Section: Fluorination Levelmentioning
confidence: 99%